2005
DOI: 10.1074/jbc.m411603200
|View full text |Cite
|
Sign up to set email alerts
|

Interaction with Type IV Pili Induces Structural Changes in the Bacterial Outer Membrane Secretin PilQ

Abstract: Type IV pili are cell surface organelles found on many Gram-negative bacteria. They mediate a variety of functions, including adhesion, twitching motility, and competence for DNA uptake. The type IV pilus is a helical polymer of pilin protein subunits and is capable of rapid polymerization or depolymerization, generating large motor forces in the process. Here we show that a specific interaction between the outer membrane secretin PilQ and the type IV pilus fiber can be detected by far-Western analysis and suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(71 citation statements)
references
References 60 publications
2
68
0
1
Order By: Relevance
“…The structure seen showed a large central cavity, which was closed at the poles by 'plug' and 'cap' features, and four 'arm' features at the sides. The results suggested that the PilQ complex is the channel through which the moving pilus fibre (polymerized PilE) is extruded and retracted from the bacterial surface (Collins et al, 2005). PilQ subunits form dodecameric complex structures that are extremely stable to heat and SDS.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…The structure seen showed a large central cavity, which was closed at the poles by 'plug' and 'cap' features, and four 'arm' features at the sides. The results suggested that the PilQ complex is the channel through which the moving pilus fibre (polymerized PilE) is extruded and retracted from the bacterial surface (Collins et al, 2005). PilQ subunits form dodecameric complex structures that are extremely stable to heat and SDS.…”
Section: Introductionmentioning
confidence: 93%
“…The findings in the non-piliated Mc-656, which produced minute amounts of PilQ multimer, most probably because it is not properly folded (Fig. 2b), might also be complicated by the fact that the conformation of the PilQ complex changes with its reaction state with its pilus substrate (Collins et al, 2005). Our findings that the mutations introduced into the Mc-656 and Mc-678 mutants compromised PilQ multimer formation and/or stability complicated the interpretation of the data obtained from these variants.…”
Section: Antibody Accessibility Of Pilq In Cellsmentioning
confidence: 99%
“…In Neisseria meningitidis, the ATPase activity of PilF is necessary to drive polymerization of the pilin subunits within the periplasm. PilF associates with PilG in a complex at the inner membrane, and the growing polymerized pilin subunits are extruded across the outer membrane through the central cavity in PilQ (Balasingham et al, 2007;Carbonnelle et al, 2006;Collins et al, 2001Collins et al, , 2005Wall et al, 1999). It is not clear how the Tfp are assembled and cross the outer membrane of F. tularensis in the absence of PilG and PilQ; no additional homologues of these proteins were found by a BLAST search.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro assays demonstrated a direct interaction between PilQ complexes and one end of purified Type IV pili [41]. A negative-stain reconstruction of the pilus-bound PilQ complex differs from the non-bound complex in that its central cavity was filled and the arms are splayed, thus dissociating the cap.…”
Section: The Outer Membrane Secretinmentioning
confidence: 99%